2018
DOI: 10.1016/j.dib.2018.08.173
|View full text |Cite
|
Sign up to set email alerts
|

Data on the early oxidation of SiO2-coated pure Ti and bulk Ti5Si3 at 800 °C

Abstract: Oxidation of pure Ti sputtered with a 250 nm layer of amorphous SiO2 and bulk Ti5Si3 was conducted at 800 °C for 2 or 32 h in a 1 standard cubic centimeter per minute (SCCM) O2/4 SCCM Ar environment (approximately pO2 = 0.2 atm/20.3 kPa). Specimens were characterized using transmission electron microscopy, scanning transmission electron microscopy, and energy dispersive spectroscopy. The data in this article accompanies research article “Early oxidation behavior of Si-coated titanium” [1], which contains furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Analogously to Ti 2 O 3 , the dispersed state of TiB 2 would be due to its partial dissolution within the glass network. Formation of Ti 5 Si 3 has been strongly suggested during the interaction of Ti with silicon-containing coatings (Si, SiO 2 , glass, ...) in previous works [8,41,42]. The presence of other silicides was also sometimes suggested, see reference [41], and references herein.…”
Section: Discussionmentioning
confidence: 85%
“…Analogously to Ti 2 O 3 , the dispersed state of TiB 2 would be due to its partial dissolution within the glass network. Formation of Ti 5 Si 3 has been strongly suggested during the interaction of Ti with silicon-containing coatings (Si, SiO 2 , glass, ...) in previous works [8,41,42]. The presence of other silicides was also sometimes suggested, see reference [41], and references herein.…”
Section: Discussionmentioning
confidence: 85%
“…Their study showed that the volume fraction of Mo 3 Si in the sample decreased with increasing Ti content and even disappeared completely in the 30Mo-40Ti-20Si-10B alloy with a phase composition of Mo ss + Mo 5 SiB 2 + Ti 5 Si 3 . Based on previous research findings, monolithic Ti 5 Si 3 demonstrates exceptional resistance to oxidation in the air up to 1250 • C [71][72][73][74]. As the unsatisfactory Mo 3 Si phase gradually disappeared and the content of the Ti 5 Si 3 phase increased, the alloy oxidation resistance at 800 • C was improved.…”
Section: Ti Element Modified Mo-si-b Alloysmentioning
confidence: 81%